Memory and Migration's Psychological Impact in “The Lion,The Witch and The Wardrobe ”- C.S Lewis - M.Priscilla; Dr.V.Lizy (Revista Electronica de Veterinaria, 2024)
Memory and Migration is typically understood to be the repository of past events within a specific local environment. Recent theories, on the other hand, have shifted the emphasis to the process of remembering, which permits the past whether communal or individual to surface as a construct that serves as a powerful motivator for identity development in any given moment. This viewpoint holds that the memory process chooses aspects of the past and transforms them into roughly cohesive structures. These structures must then be verified by others in order to fulfil their function as legitimate interpretations of the past and components of present and future identity. Consequently, memories are dialogical phenomena that are influenced by conversations or, more generally, by interactions in a variety of literature. The way that people and communities create their identities is greatly influenced by memory. This collection of writings examines how immigration, forced expulsions, exile, banishment, and war affect both individual and collective memory, even though memory is typically thought of in the context of a stable, unchanging environment. Case studies and theoretical approaches that highlight memory's malleability are used to study how memory impacts cultural representation and historical understanding across generations. Leading academics from a range of disciplines around the world contribute to the book Memory and Migration, which is really interdisciplinary. Collaboratively, the pieces effectively address the main idea and build on the research of individual writers. Memory and Migration is a pioneering contribution to a new field of study that offers important. Thus, this paper focuses on memory in the works of C.S Lewis the Chronicles of Narnia.